Accounting Disclosure Policies and their Role in Supporting Financial Inclusion: An Analytical Study of Banks in Iraq - Abdullah, Hariem Abdullah; hamad, Hawkar Anwer hamad; Rashid, Rabar Rashid (Sulaimani Journal for Humanities, 2026)
This study examines the role of accounting disclosure policies in supporting financial inclusion within the Iraqi banking sector. Using a panel dataset of 13 commercial banks listed on the Iraqi Stock Exchange over the period 2018–2023, the study applies panel regression techniques, including OLS, EGLS, and RE models. A disclosure index was developed to measure the level of accounting disclosure based on IFRS and Central Bank of Iraq requirements, while financial inclusion was assessed through indicators such as mobile banking users, new accounts opened, POS terminals, SME loan ratios, and electronic payment volumes. The results show that accounting disclosure policies have a significant positive effect on most dimensions of financial inclusion, particularly digital inclusion indicators such as mobile banking, account openings, and POS terminals. However, the relationship with e-payment volumes is weak, suggesting that other factors may influence transactional inclusion. These findings confirm that stronger disclosure practices enhance transparency and trust, thereby promoting the adoption of digital financial services in Iraqi banks. The study recommends that regulators strengthen mandatory disclosure frameworks to further advance financial inclusion and sustainable banking practices in Iraq.
Keywords: Accounting disclosure; financial inclusion; Digital banking; Iraqi banks; IFRS